Pengaruh ESG dan Green Innovation terhadap Nilai Perusahaan: Analisis Data Panel dengan Peran Mediasi Kinerja Keuangan pada Sektor Energi - Jean Stevany Matitaputty; Gracella Theotama; Alvina Damayanti (Politeknik Ganesha Medan, 2026)
This study examines the effect of ESG and green innovation on firm value, with financial performance as a mediating variable in the energy sector companies. The increasing global focus on sustainability has encouraged firms to adopt ESG practices and green innovation strategies to enchance competitiveness and attract investors. However, previous studies have reported inconsistent findings regarding the impact of ESG and green innovation on firm value, particularly in the energy sector. Therefore, this study aims to provide empirical evidence on the direct and indirect relationships among these variables. This study employs a quantitive approach using panel data with 358 samples from energy sector companies during the 2021-2024 period. The analysis applies panel data regression using the Common Effect Model to test the proposed relationships. The results show that ESG disclosure has a positive effect on firm value, indicating that investors perceive strong sustainability practices as a positive signal of long-term corporate prospects and effective risk management. In contrast, green innovation does not significantly affect firm value, suggesting that the market may not immediately recognize the economic benefits of environmentally oriented innovation activities. Furthermore, financial performance is not found to mediate the relationship beetwen ESG and firm value. This study provides implications for energy sector firms to prioritize ESG implementations as a strategy to enchance firm value.